PENGOLAHAN ARSIP DINAMIS INAKTIF KECAMATAN BANGUNTAPAN DI KANTOR ARSIP KABUPATEN BANTUL - , RIA YUNITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The writing of the final report entitled âThe Arrangement Of Inactive Records Kecamatan Banguntapan in Kantor Arsip Kabupaten Bantulâ is the result of collecting data from the practice field work carried out in Kantor Arsip Kabupaten Bantul. Field Work Practice has the purpose of knowing the condition of the inactive records and knows of inactive records Kecamatan Banguntapan and the processing procedures and the problem. The methods used in the research, such as through observation, study of the literature and interviews. The observation that do direct observation of processing of inactive records at Kantor Arsip Kabupaten Bantul. Study of the library is conducting a review of the literature with the goal of answering formulation of the problem gathering of information that is relevant to the topic of the writing of the final report. The review is intended to complete the data where is still less than perfect and get a over complete information from the speaker are experts in their field. The conclusions of the final report that The Arrangement Of Inactive Records Kecamatan Banguntapan in Kantor Arsip Kabupaten Bantul analogous with the procedure of archival science. The transfering process is in analogous with the policy in order for the conserving archival treasures. Records center and infrastructure already complete and adequate. Of to the Kantor Arsip Kabupaten Bantul can improve the preservasi of records as well as improved of the competency of human resources (HR) in the field of records education and training so that they can be culturuly in records management.